Effect of Stocking Density and Dietary Antimicrobial Inclusion of Male Broilers Grown to 35 Days of Age Part 2: Blood Physiological Variables - Olanrewaju, H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2020)
Objective: This study investigated the effects of recommended stocking densities and dietary antimicrobial inclusion of male broilers grown to 35 days of age on selected blood physiological variables. Materials and Methods: In each study, a total of 1024 1-day-old Ross×Ross 708 male chicks were randomly distributed into 32 pens based on 4 assigned stocking density treatments. The treatments consisted of 4 densities (27, 29, 33, 39 kg m–2) and 2 diets (AGP+, ABF) arranged in a 4×2 factorial with eight replicates. Conventional (antimicrobial-growth-promoters, AGP+) and antibiotic free (ABF) diets were equally assigned to each pen with feed and water provided ad libitum. Blood samples were collected from the brachial wing vein of 3 birds per pen on day 15, 28 and 35, which were then analyzed immediately for whole blood physiological variables. Blood plasma samples were analyzed for T3, T4 and corticosterone. Results: Results show there was no effect of stocking density on any of the selected physiological variables. However, in comparison to broilers fed with ABF diet, broilers with AGP+ had significant higher levels of pO2, sO2, SaO2, Ca2+ and K+ which were within physiological ranges. In addition, blood glucose and plasma corticosterone concentrations were not affected by treatments, suggesting an absence of physiological stress. Conclusion: In conclusion, Stocking densities up to 39 kg m–2 with appropriate environmental management regardless of antimicrobial addition in the diets may be suitable for both poultry integrators and contract growers to enhance broilers production efficiency without compromising the welfare of broilers grown to 35 days of age.